NMR Study of Photo-Oxidation of Styrene - Kamba, Emmanuel Alhassan; Daniel, Emmanuel Baaku Attah (Darul Yasin Al Sys, 2024)
In this study, CeO2 and several Co metal ions doped CeO2 were synthesized through hydrothermal method and tested for photocatalyzed oxidation of styrene. The characterization data obtained on XRD, EDX and SEM showed the formation process of the synthesized nanoparticles of various sizes as well as the structure of the crystals. Catalyst immobilization technique was utilized to perform a “pseudo” in-situ photo-oxidation of styrene using NMR spectroscopy. Using molecular oxygen as the oxidant, 0.3 mol % Co-doped CeO2 showed the highest conversion of 45 % while the selectivities for styrene oxide and benzaldehyde were 38 % and 51 % respectively. As revealed by the kinetic study in this work, the photo-oxidation reaction proceeded according to Langmuir-Hinshelwood model. The synthesized catalyst showed high stability and reusability over several photo-oxidation cycles. CeO2 is indeed a promising catalyst ideal for photo-oxidation reactions to produce styrene oxide.